Aliens : Is Anybody Out There? - Kocienda, Genevieve (NewYork Cambridge University, 2014)
Are humans alone in the universe, or is intelligent life out there somewhere? Find out how people throughout the years have explored this age-old question.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: Pre-Intermediate Level; English language